A pilot study for measuring correlations between hormone levels and risk taking in men and women at different times of day. (1st January 2012) - Oran, Jale S.; Akyatan, Ayça
Risk taking is a part of life, and people take risks in different contexts. Risk taking is mostly associated with aggression. Numerous studies have explored differences in risk taking between the genders. In addition, the relationships between risk taking and the hormones cortisol and testosterone have recently attracted attention. There were two main objectives of this study. First, we looked for correlations between risk-taking behaviour and the hormones cortisol, testosterone and estradiol. Second, we asked whether gender and/or time of day impacted these correlations. The subjects were undergraduate students in the Business Administration Department of Marmara University. We found a significant correlation in one category. However, when we compared the correlations across sessions and genders, we found that risk taking was more strongly associated with testosterone and cortisol in men than in women and that hormones and risk taking were more strongly associated in the afternoon than in the morning.